2008
DOI: 10.3844/ajabssp.2008.639.646
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Physicochemical and Thermorheological Properties of Sago Starch

Abstract: This study was a part of a research project aiming to investigate the texture characteristics of protein -starch interaction in fish based product keropok lekor. Accordingly, the current review study focused on some physicochemical (molecular weight, viscosity, chemical composition and swelling power) and thermorheological (gelatinization, retrogradation and viscoelsticity) characteristics of sago starch alone and in mixtures with other ingredients such as sucrose, salts and hydroclloids. The inferred outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 70 publications
1
15
0
2
Order By: Relevance
“…Siau et al (2004) attempted to make cationic sago starch using 3-chloro-2-hydroxypropyltrimethylammonium chloride (0.01-0.10 mol L −1 ) and sodium hydroxide (0.03-0.86 mol L −1 ) and found that the gelatinization enthalpy of cationic sago starch was lower, compared with native sago starch. The enthalpy of a transition is explained as corresponding to the amount of crystal order (or double helical structure) in the starch suspension (Mohamed et al 2008). The structural transformation of sago starch modified by osmotic pressure and heat moisture was observed by DSC (Pukkahuta and Varavinit 2007).…”
Section: Gelatinization Characteristics Of Sago Starchmentioning
confidence: 99%
“…Siau et al (2004) attempted to make cationic sago starch using 3-chloro-2-hydroxypropyltrimethylammonium chloride (0.01-0.10 mol L −1 ) and sodium hydroxide (0.03-0.86 mol L −1 ) and found that the gelatinization enthalpy of cationic sago starch was lower, compared with native sago starch. The enthalpy of a transition is explained as corresponding to the amount of crystal order (or double helical structure) in the starch suspension (Mohamed et al 2008). The structural transformation of sago starch modified by osmotic pressure and heat moisture was observed by DSC (Pukkahuta and Varavinit 2007).…”
Section: Gelatinization Characteristics Of Sago Starchmentioning
confidence: 99%
“…According Olayinka et al [13] will increase the drying process chain association between amylose-amylose starch and amyloseamylopectin in amorf area, separate amylose and amylopectin fractions, increasing the cohesiveness of the material in the granules due to the interaction and pressure. In the process of heating the hydrogen bonds that stabilize the double helix structure in crystalline disconnected and replaced by water [12].…”
Section: Effect Of Playback Speed Capacity Dryer Feed and Air Tempermentioning
confidence: 99%
“…Siau et al (2004) attempted to make cationic sago starch using 3-chloro-2-hydroxypropyltrimethylammonium chloride (0.01-0.10 mol L ) and found that the gelatinization enthalpy of cationic sago starch was lower, compared with native sago starch. The enthalpy of a transition is explained as corresponding to the amount of crystal order (or double helical structure) in the starch suspension (Mohamed et al 2008). The structural transformation of sago starch modified by osmotic pressure and heat moisture was observed by DSC (Pukkahuta and Varavinit 2007).…”
Section: Gelatinization Characteristics Of Sago Starchmentioning
confidence: 99%